OSCER State of the Center Address 2015 - Neeman, Henry (My University, 2015)
The OU Supercomputing Center for Education & Research (OSCER) celebrated its 14th anniversary on August 31 2015. In this report, we examine what OSCER is, what OSCER does, what OSCER has accomplished in its 13 years, and where OSCER is going.
Biography Dr. Henry Neeman is the Director of the OU Supercomputing Center for Education & Research, Assistant Vice President Information Techology – Research Strategy Advisor, Associate Professor in the College of Engineering and Adjunct Associate Professor in the School of Computer Science at the University of Oklahoma. He received his BS in computer science and his BA in statistics with a minor in mathematics from the State University of New York at Buffalo in 1987, his MS in CS from the University of Illinois at Urbana-Champaign in 1990 and his PhD in CS from UIUC in 1996. Prior to coming to OU, Dr. Neeman was a postdoctoral research associate at the National Center for Supercomputing Applications at UIUC, and before that served as a graduate research assistant both at NCSA and at the Center for Supercomputing Research & Development. In addition to his own teaching and research, Dr. Neeman collaborates with dozens of research groups, applying High Performance Computing techniques in fields such as numerical weather prediction, bioinformatics and genomics, data mining, high energy physics, astronomy, nanotechnology, petroleum reservoir management, river basin modeling and engineering optimization. He serves as an ad hoc advisor to student researchers in many of these fields. Dr. Neeman's research interests include high performance computing, scientific computing, parallel and distributed computing and computer science education.
Now in its 13th year, the Oklahoma Supercomputing Symposium is the oldest annual event of its kind in an EPSCoR jurisdiction. Attendance in 2014 was 271: 85 (31%) from OU, 186 (69%) non-OU (or unstated) 184 (68%) academic, 87 (32%) non-academic (or unstated) 28 academic institutions in 8 states 29 commercial firms 9 government agencies (federal and state) 4 non-governmental organizations 171 (63%) Oklahoman, 100 (37%) non-Oklahoman (or unstated) 217 (80%) from EPSCoR jurisdictions, 54 (20%) not from EPSCoR jurisdictions (or unstated) The 13 Symposia to date have had aggregate attendance over 3000, from: 112 academic institutions from 27 US states and territories including 61 academic institutions from 14 EPSCoR jurisdictions 143 private companies 37 government agencies (federal, state, municipal, foreign) 20 non-governmental organizations
Keywords: Computer Science.; Supercomputing; High-performance computing